The unique dielectricity of inorganic perovskites toward high-performance triboelectric nanogenerators. (March 2020) - Wang, Yudi; Duan, Jialong; Yang, Xiya; Liu, Liqiang; Zhao, Leilei; Tang, Qunwei
Abstract: Inorganic cesium lead tri-bromine (CsPbBr3 ) perovskite is a star material in modern optoelectronic and electronic nanodevices due to its fascinating optical and electronic properties and excellent stability in atmosphere. However, the unique dielectric behavior still remains to be exploited. Herein, inorganic CsPbBr3 perovskite is introduced into triboelectric nanogenerators for the first time in view of its tremendous dielectric and electrical properties. Electron binding energy, dielectric properties and surface potentials are systematically optimized through doping Ba 2+ into CsPbBr3 lattice to form CsPb1-x Bax Br3 ( x  = 0.01–0.13) perovskites. The output performances are significantly improved on account of enhanced space charge polarization and increased work function. An open-circuit voltage of 220 V, short-circuit current density of 22.8 mA m −2 and maximized power density of 3.07 W m −2 are registered by the champion CsPb0.91 Ba0.09 Br3 based TENG with lighting up over 80 LED lights. Finally, impacts of temperature and relative humidity on the output performance of perovskite TENG are investigated, high durability and stability of the perovskite TENGs are presented indicating the remarkable reversibility and adaptability of all-inorganic CsPbBr3 perovskites in TENG for mechanical energy harvesting. Graphical abstract: Image 1 Highlights: Unique dielectric property of all-inorganic CsPbBr3 perovskite is introduced into TENG for mechanical energy harvesting. The impacts of Ba 2+ dosages on electron binding energy, dielectric properties and surface potentials are studied. Significant output enhancement can be achieved through enhanced space charge polarization and increased work function. The optimized TENG achieves an ultrahigh V oc of 220 V, J sc of 22.8 mA m −2 and maximized power density of 3.07 W m −2 . The perovskite TENGs present Highly stable performances under harsh environment at ambient air atmosphere.